2007
DOI: 10.1007/s10695-007-9132-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ration size on growth, body composition, and energy and protein maintenance requirement of fingerling Indian major carp, Labeo rohita (Hamilton)

Abstract: An eight-week feeding trial has been conducted to determine the optimum ration for Indian major carp, Labeo rohita, fingerling (4.10 ± 0.30 cm, 0.55 ± 0.16 g) by feeding a purified diet (40% CP; 3.61 kcal g -1 GE) at six levels, 2, 4, 6, 8, 10, and 12% of body weight per day, at 0800 and 1600 h, in triplicate, to 20 fish per trough fitted with a water flow-through system. Highest weight gain, best feed conversion ratio (FCR), best specific growth rate (SGR%), and highest protein efficiency ratio (PER) were evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 77 publications
3
19
1
Order By: Relevance
“…Hassan and Jafri (1994) reported gradual decline in conversion efficiency in fish fed at higher ration levels in Clarias batrachus. Ahmed (2007b) also reported similar result in Indian major carp, Labeo rohita. In the present study, a similar trend in feed conversion efficiency was also noticed in H. fossilis fed at higher ration levels than optimum.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Hassan and Jafri (1994) reported gradual decline in conversion efficiency in fish fed at higher ration levels in Clarias batrachus. Ahmed (2007b) also reported similar result in Indian major carp, Labeo rohita. In the present study, a similar trend in feed conversion efficiency was also noticed in H. fossilis fed at higher ration levels than optimum.…”
Section: Discussionsupporting
confidence: 64%
“…A semi-moist diet was prepared using the ingredients listed in Table 1 and cut in the form of small cubes, packed in airtight polythene bags and stored in a frost-free deep freezer at -20°C until use. The other details for the preparation of diet used in the present study is as previously lined in Ahmed (2007b). Since digestible or metabolizable energy values for the ingredients used are not available for H. fossilis, physiological fuel values of 4.5, 3.5 and 8.5 kcal g -1 for protein, carbohydrate and fat, respectively (Jauncey 1982), were utilized to calculate the energy content of the diet.…”
Section: Experimental Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcass water, protein, and lipid content, liver water and lipid content, and liver and spleen size, were not affected by music transmission and are in accordance with previously reported effects of music on common carp (Papoutsoglou et al 2007). However, in the current study lower carcass ash content were observed in music-treated fish, possibly reflecting the higher body weight achieved and indicating a different flesh to skeleton ratio (Ahmed 2007). On the other hand, the current liver composition results contrast with those observed for music-treated gilthead sea bream .…”
Section: Discussioncontrasting
confidence: 54%
“…Apart from that, feed rate could also affect body composition of fish (Ahmed 2007;Kim et al 2012). The results showed that gross body composition of fish fed with 50-100% CM inclusion level showed significantly higher crude protein content than those fed with lower inclusion of CM.…”
Section: Fishmealmentioning
confidence: 99%